Representative bureaucracy and unconscious bias: Exploring the unconscious dimension of active representation. (26th October 2017) - Akram, Sadiya
Abstract : Representative bureaucracy theory explores the effects of representation on bureaucracies, but less attention has been paid to date as to how agents represent values or interests. Addressing this omission, this article highlights the unconscious dimension of active representation and, more specifically, the role of unconscious bias in representation. Unconscious bias has received limited attention to date in public administration, but has clear relevance for understanding how representation occurs at the individual level. This article proposes a framework for understanding unconscious bias. Drawing on Bourdieu's habitus, but making explicit its unconscious dimension, I argue that unconscious bias enhances our understanding of how active representation occurs in bureaucracies today. The article applies these insights to the case of unconscious gender bias as found in the Australian Public Service (APS) and concludes by exploring the methodological challenges involved in building a research agenda into tackling unconscious bias.